(3GdNUGFU GdSjcheJQjI ddUjZI GdYQHjI debjGS gGdjfLQ aj GdEOGQI GdJYdjejI,s - (3GdehShj, fYeGf eMeO UGdMs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2001)
(3JgOa gPg GdOQGSI Edi JWhjQ UjZI YQHjI debjGS gGdjfLQ ddSdhc GdEOGQj hGdJYdjej deOjQ GdeOQSI hGdJMbb ef UOb GdebjGS hKHGJg hGdbOQI GdJejjRjI dabQGJg(B. (3jWQM GdHGMK EWGQ GdOQGSI ef NdGd(B: 1) (3GdHMK aj GdJMhdGJ GdJj CUGHJ eaghe eOjQ GdeOQSI, hUhdkG Edi GdEOGQI GdaGYdI, (B2) (3GdHMK aj GdCOhGJ GdeSJNOeI dJbhje COGA GdeOjQ YQHjkG hYGdejkG, (B3) (3eMGhdGJ GdHMQjf aj JWhjQ GdEOGQI GdeOQSjI, (B4) (3GdOQGSGJ GdSGHbI GdJj HMKJ GdehVhY, (B5) (3YQV NdajGJ hechfGJ ebjGS gGdjfLQ hejRGJg hCgejI hVY UjZI YQHjI dg(B. (3Ke JYQV GdOQGSI GdNWhGJ GdJj GJHYJ dEYOGO gPg GdUjZI hPdc HJWHjb GdebjGS Ydi (B185 (3eYdekG heYdeI aj GdeOGQS GdKGfhjI aj OhdI GdHMQjf(B. (3JNdU Edi Cf GdUjZI GdYQHjI debjGS gGdjfLQ JJeJY HNUGFU SjcheJQjI JLYdgG COGI ehKhbI jecf GSJNOGegG dJbhje COGA GdeOjQ, hJhUj HGdEaGOI efgG aj JMOjO aGYdjI GdEOGQI GdJYdjejI aj eNJda GdOhd GdYQHjI(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Administration Scolaire; Educational administration; (3GdGOGQI GdJQHhjIs